Oncogenic Osteomalacia due to FGF23-Expressing Colon Adenocarcinoma - Leaf, David E. (Endocrine Society, 2013)
CONTEXT: Oncogenic osteomalacia, a paraneoplastic syndrome associated with hypophosphatemia due to increased urinary phosphate excretion, is caused by excessive synthesis and secretion of fibroblast growth factor 23 (FGF23), a phosphaturic hormone that is normally produced by osteocytes. Most cases of oncogenic osteomalacia have been associated with benign tumors of bone or soft tissue; however, whether malignant neoplasms can also produce and secrete FGF23 is currently unknown. OBJECTIVE: The aim was to determine whether a malignant neoplasm could cause oncogenic osteomalacia through excessive production and secretion of FGF23. SETTING: We describe an 80-year-old woman with stage IV colon adenocarcinoma who presented with severe hypophosphatemia (0.4 mg/dL; reference, 2.6–4.5 mg/dL). RESULTS: Fractional excretion of phosphate was 34% (reference, <5% in the setting of hypophosphatemia), and plasma levels of FGF23 were highly elevated at 674 RU/mL (reference, <180 RU/mL). Immunohistochemical analysis of the patient's tumor showed strong staining for FGF23. Genetic analyses revealed a point mutation in the KRAS gene. CONCLUSIONS: We present the first case in which a malignant neoplasm is documented to produce and secrete FGF23, leading to renal phosphate-wasting. Oncogenic osteomalacia should be considered in the differential diagnosis for patients with a malignant tumor who present with hypophosphatemia.